Anatomic Variations Important for Dental Implantation in the Mandible—A Systematic Review - Zlata Rajkovic Pavlovic; Milos Stepovic; Marija Bubalo; Ivana Zivanovic Macuzic; Maja Vulovic; Nevena Folic; Jovana Milosavljevic; Valentina Opancina; Dobrivoje Stojadinovic (Diagnostics)
Background: This is a systematic review on the subject of anatomic landmarks and variations in the mandible that influence implantation placement. With this systematic review, we would like to summarize the results from different studies that are relevant to this subject and that are up to date, presenting their main findings, the measurements of mentioned landmarks, and giving clinical implications that will be helpful to practitioners in their better understanding of this topic. Methods: This study followed all of the elements of PRISMA. The criteria for inclusion and exclusion are described in detail. The following bibliographic databases were searched: PubMed (MEDLINE), The Cochrane Library, Wiley Online Library, EMBASE, and, additionally, Google Scholar. The search of articles was carried out using a combination of different keywords with a Boolean operator for each keyword. A total of 30 studies were included in this review and the risk of bias for each study was assessed. This review was registered with the PROSPERO ID number CRD42024609308. Results: The structure “SPIDER“ was used to present the findings in the summation table, followed by a detailed description of the quantitative findings and overall mean values of the most commonly used measured points. The morphometric measurements of anatomic details and variations in the mandible, such as the mandibular canal, mental foramen, lingual foramina, lingual canal, incisive canal, and mandibular concavity, are of high significance for clinicians dealing with implantation where gender, ethnicity, age groups, the side of the mandible, or remaining teeth can influence implantation planning. Conclusions: The distances of the named anatomic landmarks to the surrounding bone structures that are used as a guide during planning are of huge importance, so proper and detailed measurements must be executed by experienced professionals using CBCT. Knowledge of the position and variation in these landmarks may be used for any bone-guided augmentation, surgical transpositions of anatomic landmarks, and surgery intervention planning. The results of this study can aid in choosing appropriate measurement points and give the gross picture, for clinicians, in therapy planning, considering all the landmarks of significance in the mandible.